Ag Thin Film Dewetting Prevention by Ion Implantation. Issue 11 (3rd May 2019) - Chi, Longxing; Bassim, Nabil
Abstract: Ion implantation is applied here to prevent metallic silver (Ag) thin films from dewetting on a sapphire substrate during annealing. In these experiments, silicon (Si) and indium (In) atoms are implanted into Ag thin films grown directly on sapphire, which are then annealed for different time periods to introduce film dewetting. It is observed that trace amounts of 10 14 cm −2 dopants significantly retard the film grain growth, alter the film surface wetting features, and trivially influence the electrical and optical performance of the original film. A grain growth model with the presence of solute species is introduced here, combined with a thermodynamic simulation of film dewetting. It is found that doping ions introduce solute drag into Ag grains thereby significantly retarding the grain growth by generating a limiting grain size. The shrunken grains then alter the film surface energy distribution, transferring the most stable state from the dewetting phase to the wetting phase. The approach provides a novel strategy to suppress metallic thin films from dewetting with high stability, durability, and insignificant impact on the film performance without using an adhesion layer and also potentially expands the thermal processing window for metallic thin films. Abstract : Ion implantation of Si and In dopants is applied to prevent nanoscale Ag thin films from dewetting upon thermal annealing. Modified grain growth model and thermodynamic wetting models of Ag grains are proposed and combined to explain and predict grain growth behavior and wetting behavior of Ag thin films with implantation upon annealing.